Endovascular conduit fenestration closure after extracardiac total cava-pulmonary anastomosis operation - Kuzmenko, Yu. L.; Maksimenko, A. V.; Dovgaluk, A. A.; Radchenko, M. P.; Motrechko, A. A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
This article represents the experience of percutaneous closure of extracardiac conduit fenestration in 6 patients after Fontan operation and detailed analysis of hemodynamic changes after the procedure.